Exploratory Investigation of Intestinal Structure and Function after Stroke in Mice - Diya Ye; Yuting Hu; Ning Zhu; Weizhong Gu; Gao Long; Enfu Tao; Marong Fang; Mizu Jiang (Mediators of Inflammation)
Stroke is the second leading cause of death worldwide. Patients who have a stroke are susceptible to many gastrointestinal (GI) complications, such as dysphagia, GI bleeding, and fecal incontinence. However, there are few studies focusing on the GI tract after stroke. The current study is to investigate the changes of intestinal structure and function in mice after ischemic stroke. Ischemic stroke was made as a disease model in mice, in which brain and ileal tissues were collected for experiments on the 1st and 7th day after stroke. Intestinal motility of mice was inhibited, and intestinal permeability was increased after stroke. Hematoxylin-eosin (HE) staining showed the accumulation of leucocytes in the intestinal mucosa. Myeloperoxidase (MPO) activity and inflammatory proteins (nuclear factor kappa-B (NF-κB), inducible nitric oxide synthase (iNOS)) in the small intestine were significantly increased in mice after stroke. The expression of tight junction (TJ) proteins (zonula occludens-1 (ZO-1), occludin, and claudin-1) was downregulated, and transmission electron microscopy (TEM) showed broken TJ of the intestinal mucosa after stroke. Glial fibrillary acidic protein (GFAP) and the apoptosis-associated proteins (tumor necrosis factor (TNF-α), caspase-3, and cleaved caspase-3) were notably upregulated as well. Ischemic stroke led to negative changes on intestinal structure and function. Inflammatory mediators and TNF-α-induced death receptor signaling pathways may be involved and disrupt the small intestinal barrier function. These results suggest that stroke patients should pay attention to GI protection.